Draft primary school syllabus: Language Arts (A working document) - Trinidad and Tobago. Ministry of Education (Ministry of Education, 1997)
The current Language Arts and Reading Syllabuses for primary schools were issued in 1988. This presentation of “reading” and “language” as separate syllabus documents resulted, in classroom teaching practice, in a dual approach to the teaching of English – a false dichotomy between the teaching of reading and the teaching of the other language skills and components of language. In addition, performance in Standard English and achievement of the instructional objective of the current syllabuses by primary school students are less than satisfactory. This draft syllabus, which reflects contemporary thinking about the nature and purpose of language, and the processes involved in language learning and their implications for language teaching, is an attempt to address this problem. It takes a holistic and integrated approach to language and the teaching of language, and also takes account of the Trinidad vernacular or Creole, since in the Trinidad and Tobago context, standard English is to be piloted in a limited and select number of primary schools before being disseminated for full-scale implementation.
Keywords: Language education